Pt / C catalyst doped with stable metal G on surface as well as preparation method and application of Pt / C catalyst

By doping the stable metal G on the surface of the Pt/C catalyst and preparing the Pt-G/C catalyst by low-temperature annealing reduction method, the problem of insufficient activity and durability of the existing Pt/C catalyst is solved, and higher catalytic activity and stability are achieved, while reducing costs.

CN119920920AActive Publication Date: 2025-05-02HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510090634.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing Pt/C catalysts have problems of insufficient activity and durability under long-term harsh reaction conditions.

Method used

The surface-doped Pt-G/C catalyst was prepared by immersing, evaporating and adsorbing the salt solution of stable metals G (such as Au, Mo, W) on the surface of the Pt/C catalyst, and a low-temperature annealing reduction method was used to prepare the surface doped Pt-G/C catalyst.

Benefits of technology

The activity and stability of the catalyst are significantly improved, the loading of Pt is reduced, the cost is reduced, and good applicability and performance are shown in fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920920A_ABST
    Figure CN119920920A_ABST
Patent Text Reader

Abstract

The invention discloses a Pt / C catalyst doped with stable metal G on the surface and a preparation method and application of the Pt / C catalyst, and aims to solve the technical problems of poor catalytic activity and poor adaptability of the existing Pt / C catalyst. In the Pt / C catalyst doped with the stable metal G on the surface, G atoms are uniformly distributed on the surfaces of Pt particles, and G is one or more of Au, Mo and W; and the mass percentage of Pt in the catalyst is 10-30%. A salt solution of stable metal G is impregnated, evaporated to dryness and adsorbed on the surface of a Pt / C catalyst, and low-temperature annealing reduction is adopted to obtain the catalyst. The mass activity of the catalyst is 0.131 to 0.168 mA / [mu] gPt, and the half-wave potential of the catalyst is 0.896 to 0.905 V. After the fuel cell is assembled, the peak power density value is only reduced by 0.6 W after the fuel cell is aged for 30000 circles, and the stability is good. The invention can be used in fuel cell field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface-doped Pt / C catalyst and a preparation method and application thereof, and belongs to the field of new energy materials. Background Art

[0002] Pt / C materials are widely used as cathode catalysts for proton exchange membrane fuel cells (ORR) due to their good catalytic performance for oxygen reduction reaction. However, current commercial Pt / C catalysts have problems such as insufficient activity and durability in long-term operation under harsh reaction conditions. Future development will focus on improving durability as the primary goal.

[0003] Currently, commercial Pt / C catalysts are still mainly high-loaded. The cost of Pt is high, and the cost of the catalyst accounts for half of the proton exchange membrane fuel cell. In addition, the catalyst is very prone to deactivation and aging during operation, causing the growth of catalyst Pt nanoparticles, resulting in a reduction in the electrochemical active area and reduced fuel cell performance. Summary of the invention

[0004] The present invention aims to solve the technical problems of poor catalytic activity and insufficient adaptability of existing Pt / C catalysts, and provides a Pt / C catalyst doped with a stable metal G on the surface, and a preparation method and application thereof. The present invention soaks and evaporates a salt solution of a stable metal G (G = Au, Mo or W) and adsorbs it on the surface of a Pt / C catalyst, and uses low-temperature annealing reduction to obtain a Pt-G / C catalyst. The activity and stability of the catalyst are significantly higher than those of a 20% Pt / C catalyst, and the surface-doped Pt-G / C catalyst is applicable in fuel cells.

[0005] In the Pt / C catalyst with surface doped stable metal G of the present invention, G atoms are uniformly distributed on the surface of Pt particles, and G is one or more of Au, Mo and W; the mass percentage of Pt in the catalyst is 10% to 30%.

[0006] Furthermore, the molar ratio of G atoms to Pt atoms is 1:(100-10). Since Au, Mo, and W elements themselves have poor catalytic activity, excessive content can easily lead to a decrease in catalytic activity. In the G element surface doped Pt / C catalyst, the molar ratio of G atoms to Pt atoms is 1:(100-10), which improves the stability of the catalyst while reducing costs.

[0007] The preparation method of the above-mentioned Pt / C catalyst doped with the stabilizing metal G on the surface is carried out according to the following steps:

[0008] 1. Preparation of Pt / C catalyst by microwave reduction method;

[0009] 2. Adsorption of G metal salt: Wet the Pt / C catalyst and place it in the dispersion solution, and stir it ultrasonically until the catalyst is evenly dispersed to obtain a mixed solution A; then add a solution of a stable metal G salt to the mixed solution A, and after the addition is complete, obtain a mixed solution B; ultrasonically treat the mixed solution B for 0.5 to 2 hours, and then stir it at room temperature for 0.5 to 2 hours to make the mixed solution evenly dispersed; then evaporate the mixed solution B in a water bath to obtain a precursor;

[0010] 3. Preparation of Pt-G / C by annealing and reduction: Place the precursor in a high-temperature furnace, heat it to 200-600°C in a reducing atmosphere and maintain it for 4-10 hours for annealing, cool it to room temperature, grind it evenly, and obtain a Pt / C catalyst with surface doped with stable metal G, recorded as Pt-G / C.

[0011] Furthermore, the specific method for preparing Pt / C by microwave reduction is: adding the carbon carrier to the dispersion and dispersing it evenly, adding chloroplatinic acid solution, stirring evenly and adjusting the pH of the mixed solution to alkaline; using microwave to reduce Pt particles, adjusting the pH to acidic after natural cooling and stirring for 12 to 24 hours, filtering and cleaning and vacuum drying to obtain a Pt / C catalyst; the dispersion is one or more of water, ethanol, methanol, and isopropanol; the carbon powder is XC-72, ECP-600JD or BP-2000.

[0012] Furthermore, the dispersion solution in step 2 is one or more of water, ethanol, methanol, and isopropanol.

[0013] Furthermore, the solution of the G metal salt described in step 2 is prepared by dissolving chloroauric acid, gold trichloride, potassium chloroaurate, molybdate, molybdenum pentachloride, tungstate, and tungsten hexachloride in a dispersed solution.

[0014] Furthermore, in the mixed solution B described in step 2, the concentration of Pt / C is 0.5-2 g / L, and the concentration of the stable metal G salt is 0.00025-0.001 mol / L.

[0015] Furthermore, the reducing gas described in step three is a H2 / N2 mixed gas or a H2 / Ar mixed gas, and the volume ratio of H2 in the mixed gas is 3% to 15%.

[0016] The application of the above-mentioned Pt / C catalyst with surface doped stabilizing metal G is that the catalyst is used in the cathode oxygen reduction reaction (ORR) of a fuel cell.

[0017] The present invention utilizes the doping of stable metal G (G = Au, Mo, W) to effectively improve the stability of the Pt / C catalyst. The stable metal G has good electrochemical stability, and is introduced into the electrocatalyst to improve the stability of the electrocatalyst. At the same time, since the ORR catalytic activity of the Au and Mo elements themselves is poor, the present invention controls the amount of stable metal G added to avoid the reduction in catalyst activity caused by the covering of the active sites of Pt in the catalyst; in addition, the cost of elements such as Au, Mo, and W is relatively high, and excessive doping will significantly affect the cost of the catalyst. The present invention maintains the activity of the catalyst while reducing the Pt loading, and modifies it using stable metal G to prepare a Pt / C catalyst with good performance and surface doped with stable metal G. The mass activity of the catalyst is 0.131 to 0.168 mA / μg Pt , the half-wave potential reaches 0.896~0.905V. After aging for 30,000 cycles, the peak power density value of the assembled fuel cell only decreases by 0.6W, with a decrease rate of 32%, showing good stability.

[0018] The advantages of the present invention are as follows:

[0019] (1) The present invention dopes the stable metal on the surface of the Pt / C catalyst. First, the metal salt is adsorbed on the surface of the Pt / C catalyst by an impregnation evaporation method. The G salt is reduced to G metal by low-temperature annealing in a reducing atmosphere. With continuous heating, the G metal is gradually and evenly distributed on the surface of the Pt particles to obtain a Pt-G / C catalyst. This preparation method is simple and easy to implement and is suitable for industrial production.

[0020] (2) The doping amount of G metal in the present invention is very low, thus avoiding the problem of decreased activity and increased cost caused by doping with a large amount of G metal.

[0021] (3) The catalyst prepared by the present invention has high electrocatalytic activity and durability for oxygen reduction reaction in acidic medium and good applicability in fuel cells, so that the catalyst also has excellent performance in fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 is a TEM image of the Pt / C catalyst doped with stable metal Au on the surface prepared in Example 1;

[0023] Figure 2 is a spherical aberration corrected transmission electron microscopy image of the Pt / C catalyst with surface doped with stable metal Au prepared in Example 1;

[0024] Figure 3 This is an EDS line scan element distribution diagram of the Pt / C catalyst with surface doped with stable metal Au prepared in Example 1, obtained by spherical aberration correction transmission electron microscopy;

[0025] Figure 4 Example 1 Preparation of Pt-Au 0.05 / C-400℃6h catalyst, Pt-Au prepared in Example 2 0.05 / C-600℃4h catalyst, 20%Pt / C catalyst prepared in step 1 of Example 1 and Pt-Au prepared in comparative example 1 0.05 / C-400℃2h catalyst XRD spectrum;

[0026] Figure 5 Example 4 Preparation of Pt-Mo 0.05 / C-400℃6h catalyst, Example 5 Preparation of Pt-W 0.1 / C-400℃6h catalyst XRD spectrum;

[0027] Figure 6 The Pt-Au prepared in Example 1 0.05 / C-400℃6h catalyst, Pt-Au prepared in Example 2 0.05 / C-600℃4h catalyst, Example 3 Preparation of Pt-Au 0.03 / C-400℃6h catalyst, Example 4 Preparation of Pt-Mo 0.05 / C-400℃6h catalyst, Example 5 Preparation of Pt-W 0.1 / C-400℃6h catalyst, 20%Pt / C catalyst prepared in step 1 of Example 1 and Pt-Au prepared in comparative example 1 0.05 / C-ORR polarization diagram of the catalyst at 400℃ for 2h;

[0028] Figure 7 The Pt-Au prepared in Example 1 0.05 / C-400℃6h catalyst, Pt-Au prepared in Example 2 0.05 / C-600℃4h catalyst, Example 3 Preparation of Pt-Au 0.03 / C-400℃6h catalyst, Example 4 Preparation of Pt-Mo 0.05 / C-400℃6h catalyst, Example 5 Preparation of Pt-W 0.1 / C-400℃6h catalyst, 20%Pt / C catalyst prepared in step 1 of Example 1 and Pt-Au prepared in comparative example 1 0.05 / C-400℃2h catalyst mass activity diagram;

[0029] Figure 8 The Pt-Au prepared in Example 1 0.05 ORR polarization diagrams of the catalyst heated at 400°C for 6h and the 20% Pt / C catalyst prepared in step 1 of Example 1 before and after aging;

[0030] Fig. 9 The Pt-Au prepared in Example 1 0.05 Mass specific activity diagram of the catalyst heated at 400℃ for 6h and the 20% Pt / C catalyst prepared in step 1 of Example 1 before and after aging;

[0031] Fig.10 The Pt-Au prepared in Example 1 0.05 Polarization diagram of the fuel cell before and after aging of the catalyst heated at 400℃ for 6h and the 20% Pt / C catalyst prepared in step 1 of Example 1. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention that does not depart from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0033] Example 1: The preparation method of the Pt / C catalyst doped with stable metal Au on the surface of this example is carried out according to the following steps:

[0034] 1. Preparation of Pt / C by microwave reduction: 48 mg of ECP-600ID carbon carrier was dispersed in 40 ml of ethylene glycol, 1.26 ml of 0.0486 mol / L chloroplatinic acid solution was added, ultrasonic treatment was performed for 1 h, and then stirred evenly with 1 mol L -1 The pH value of the mixed solution was adjusted to 12 by using NaOH-ethylene glycol solution and nitrogen was introduced to expel the dissolved air in the solution to protect the solution; the mixed solution was then placed in a microwave oven and heated for 80 seconds; after natural cooling, the pH value of the mixed solution was adjusted to 2 by using nitric acid-ethylene glycol solution and stirred for 8 hours, filtered and washed 3 times, and then vacuum dried at 80°C for 8 hours, and ground evenly to obtain a Pt / C catalyst; recorded as a 20% Pt / C catalyst;

[0035] 2. Au adsorption: 60 mg 20% ​​Pt / C catalyst was moistened and then added to 60 ml ethanol for dispersion, ultrasonicated for 30 min, and stirred until the catalyst was evenly dispersed to obtain a mixed solution A; then 0.344 ml of 1.7429 mg Au / ml HAuCl4 ethanol solution was added dropwise to obtain a mixed solution B; the mixed solution B was subjected to ultrasonic treatment for 1 hour, and then the mixed solution B was rotary evaporated to dryness in a water bath at 60°C, and ground evenly to obtain a precursor;

[0036] 3. Preparation of Pt-Au by Annealing Reduction 0.05 / C: The precursor of step 2 was placed in a high-temperature furnace, heated to 400 °C in a H2-Ar reducing atmosphere for 6 h for annealing, cooled to room temperature, and ground evenly to obtain a Pt / C catalyst doped with Au on the surface, denoted as Pt-Au 0.05 / C-400℃6h, the mass percentage of Pt in the catalyst is 20%, and the atomic ratio of Pt to Au is 20:1.

[0037] In this example, Pt-Au was prepared 0.05 TEM of the catalyst at 400℃ for 6h Figure 1 As shown by Figure 1 It can be seen that the Pt particles are evenly distributed on the carbon support.

[0038] Pt-Au prepared in Example 1 0.05 Spherical aberration electron microscopy scanning image of the catalyst at 400℃ for 6h Figure 2 As shown, from Figure 2 It can be seen that the lattice spacing of the particles is 0.227nm, which is the same as that of the Pt(111) crystal plane. Figure 3 The Pt-Au prepared in Example 1 0.05 / C-400℃6h catalyst EDS line scan element distribution diagram of spherical aberration corrected transmission electron microscope. It can be seen from the line scan that Au element is mainly distributed on the surface of Pt particles.

[0039] Example 2: The difference between this example and Example 1 is that the annealing temperature in step 3 is 600°C and the annealing time is 4 hours. The other steps and parameters are the same as those in Example 1. The obtained catalyst is recorded as Pt-Au 0.05 / C-600℃4h.

[0040] Comparative Example 1: The difference between this comparative example and Example 1 is that the annealing temperature in step 3 is 400°C and the annealing time is 2h. The other steps and parameters are the same as those in Example 1. The obtained catalyst is recorded as Pt-Au 0.05 / C-400℃2h.

[0041] Example 1 Preparation of Pt-Au 0.05 / C-400℃6h catalyst, Pt-Au prepared in Example 2 0.05 / C-600℃4h catalyst, 20%Pt / C catalyst prepared in step 1 of Example 1 and Pt-Au prepared in comparative example 1 0.05 The XRD spectrum of the catalyst at 400℃ for 2h is shown in Figure 4 As shown by Figure 4It can be seen that the heat treatment time of Comparative Example 1 is shorter, and there is an obvious PtAu alloy peak in XRD, while the heating time of Examples 1 and 2 is relatively long, and no PtAu alloy peak is observed in XRD, which proves that the Au element is evenly distributed on the surface of the Pt particles and has no effect on the crystal form of the Pt particles.

[0042] Example 3: The preparation method of the Pt / C catalyst doped with stable metal Au on the surface of this example is carried out according to the following steps:

[0043] 1. Preparation of Pt / C by microwave reduction: 48 mg of ECP-600JD carbon carrier was dispersed in 40 ml of ethylene glycol solution, 1.26 ml of 0.0486 mol / L chloroplatinic acid solution was added, ultrasonic treatment was performed for 1 h, and then stirred evenly with 1 mol L -1 The pH value of the mixed solution was adjusted to 12 with NaOH-ethylene glycol solution and nitrogen was introduced to expel the dissolved air in the solution to protect the solution; the mixed solution was then placed in a microwave oven for microwave heating for 80 seconds; after natural cooling, the pH value of the mixed solution was adjusted to 2 with nitric acid-ethylene glycol solution and stirred for 8 hours, filtered and washed 3 times, and then vacuum dried at 80°C for 8 hours, and ground evenly to obtain a Pt / C catalyst;

[0044] 2. Au adsorption: 60 mg Pt / C catalyst was moistened and then added to 60 ml ethanol for dispersion, ultrasonic treatment was performed for 30 min, and stirring was performed until the catalyst was evenly dispersed to obtain a mixed solution A; then 0.207 ml of 1.7429 mg Au / ml HAuCl4 ethanol solution, after completion of the dropwise addition, a mixed solution B is obtained; the mixed solution B is subjected to ultrasonic treatment for 1 hour, and then the mixed solution B is rotary evaporated to dryness in a water bath at 80°C, and ground evenly to obtain a precursor;

[0045] 3. Preparation of Pt-Au by Annealing Reduction 0.03 / C: The precursor of step 2 was placed in a high-temperature furnace, heated to 400°C and maintained for 6 h for annealing in a H2-Ar reducing atmosphere (H2 volume percentage is 5%), cooled to room temperature, and ground evenly to obtain a Pt / C catalyst with surface doped with stable metal Au, denoted as Pt-Au 0.03 / C-400℃6h. The mass percentage of Pt in the catalyst is 20%, and the atomic ratio of Pt to Au is 100:3.

[0046] Example 4: The preparation method of the Pt / C catalyst doped with stable metal Mo on the surface of this example is carried out according to the following steps:

[0047] 1. Preparation of Pt / C by microwave reduction: 48 mg of ECP-600JD carbon carrier was dispersed in 40 ml of ethylene glycol solution, 1.26 ml of 0.0486 mol / L chloroplatinic acid solution was added, ultrasonic treatment was performed for 1 h, and then stirred evenly with 1 mol L -1 The pH value of the mixed solution was adjusted to 12 with NaOH-ethylene glycol solution and nitrogen was introduced to expel the dissolved air in the solution to protect the solution; the mixed solution was then placed in a microwave oven for microwave heating for 80 seconds; after natural cooling, the pH value of the mixed solution was adjusted to 2 with nitric acid-ethylene glycol solution and stirred for 8 hours, filtered and washed 3 times, and then vacuum dried at 80°C for 8 hours, and ground evenly to obtain a Pt / C catalyst;

[0048] 2. Adsorption of Mo: 60 mg of Pt / C catalyst was moistened and then added with 60 ml of ethanol for dispersion, ultrasonically treated for 30 min, and stirred until the catalyst was evenly dispersed to obtain a mixed solution A; then an aqueous solution containing 0.003 mmol of sodium molybdate was added dropwise to the mixed solution A, and after the addition was complete, a mixed solution B was obtained; the mixed solution B was ultrasonically treated for 1 h, and then the mixed solution B was rotary evaporated to dryness in a water bath at 60°C, and ground evenly to obtain a precursor;

[0049] 3. Preparation of Pt-Mo by Annealing Reduction 0.05 / C: The precursor of step 2 was placed in a high-temperature furnace, heated to 400°C in a H2-Ar reducing atmosphere (H2 volume percentage is 5%), maintained for 6 hours for annealing, cooled to room temperature, and ground evenly to obtain a Pt / C catalyst doped with stable metal Mo on the surface, denoted as Pt-Mo 0.05 / C-400℃6h, in which the mass percentage of Pt is 20%, and the atomic ratio of Pt to Mo is 20:1.

[0050] Example 5: The preparation method of the Pt / C catalyst doped with the stable metal W on the surface of this example is carried out according to the following steps:

[0051] 1. Preparation of Pt / C by microwave reduction: 48 mg of ECP-600JD carbon carrier was dispersed in 40 ml of ethylene glycol solution, 1.26 ml of 0.0486 mol / L chloroplatinic acid solution was added, ultrasonic treatment was performed for 1 h, and then stirred evenly with 1 mol L -1 The pH value of the mixed solution was adjusted to 12 with NaOH-ethylene glycol solution and nitrogen was introduced to expel the dissolved air in the solution to protect the solution; the mixed solution was then placed in a microwave oven for microwave heating for 80 seconds; after natural cooling, the pH value of the mixed solution was adjusted to 2 with nitric acid-ethylene glycol solution and stirred for 8 hours, filtered and washed 3 times, and then vacuum dried at 80°C for 8 hours, and ground evenly to obtain a Pt / C catalyst;

[0052] 2. Adsorption of W: Wet 60 mg Pt / C catalyst, add 60 ml ethanol to disperse, ultrasonically treat for 30 min, stir until the catalyst is evenly dispersed, and obtain mixed solution A; then add ethanol solution containing 0.006 mmol tungsten silicate to mixed solution A, and after the addition is complete, obtain mixed solution B; ultrasonically treat mixed solution B for 1 h, then rotary evaporate mixed solution B in a water bath at 80 ° C, grind evenly, and obtain a precursor;

[0053] 3. Preparation of Pt-W by Annealing Reduction 0.1 / C: The precursor of step 2 was placed in a high-temperature furnace, annealed at 400°C for 6 h in a H2-Ar reducing atmosphere (H2 volume percentage is 5%), cooled to room temperature, and ground evenly to obtain a Pt / C catalyst doped with stable metal W on the surface, denoted as Pt-W 0.1 / C-400℃6h, the mass percentage of Pt in the catalyst is 20%; the atomic ratio of Pt to W in the catalyst is 10:1.

[0054] Example 4 Pt-Mo prepared 0.05 / C-400℃6h and Pt-W prepared in Example 5 0.1 / C-400℃6h XRD spectrum Figure 5 As shown, from Figure 5 It can be seen that after adding Mo and W elements, the crystal form of the Pt particles of the catalyst did not change.

[0055] The Pt-Au prepared in Example 1 0.05 / C-400℃6h catalyst, Pt-Au prepared in Example 2 0.05 / C-600℃4h catalyst, Example 3 Preparation of Pt-Au 0.03 / C-400℃6h catalyst, Example 4 Preparation of Pt-Mo 0.05 / C-400℃6h catalyst, Example 5 Preparation of Pt-W 0.1 / C-400℃6h catalyst, 20%Pt / C catalyst prepared in step 1 of Example 1 and Pt-Au prepared in comparative example 1 0.05 / C-400℃2h catalyst was prepared into electrode, and ORR polarization test was carried out. The method of preparing each catalyst into electrode is as follows: weigh 2.5mg catalyst, then add 500μL dispersion liquid, wherein the dispersion liquid is mixed with anhydrous ethanol, ultrapure water and nafion solution, and ultrasonicate for 1h to obtain uniformly dispersed catalyst slurry; use a micropipette to transfer 10μL catalyst slurry and drop it on the glassy carbon electrode, and the loading density of the catalyst on the electrode is 0.2mg cm -2Finally, the electrodes were dried at room temperature to obtain the electrodes, and then electrochemical tests were performed. The CHI-760e electrochemical workstation was used, the test temperature was 25°C, the test system was a three-electrode working system, and the electrolyte was 0.1 molL -1 HClO4 solution, rotating disk ring disk glassy carbon electrode as working electrode, carbon rod as counter electrode, reversible hydrogen electrode RHE as reference electrode. The ORR polarization curve is shown in the figure below. Figure 6 The mass activity diagram is shown in Figure 7 The mass activity and half-wave potential of each catalyst are shown in Table 1.

[0056] Table 1 Mass activity and half-wave potential of the catalysts prepared in each example

[0057] Example Product Name <![CDATA[Mass activity (mA / μg Pt )]]> Half-wave potential (V) Example 1 <![CDATA[Pt-Au 0.05 / C-400℃6h]]> 0.168 0.905 Example 2 <![CDATA[Pt-Au 0.05 / C-600℃4h]]> 0.135 0.896 Example 3 <![CDATA[Pt-Au 0.03 / C-400℃6h]]> 0.138 0.898 Example 4 <![CDATA[Pt-Mo 0.05 / C-400℃6h]]> 0.165 0.903 Example 5 <![CDATA[Pt-W 0.1 / C-400℃6h]]> 0.131 0.896 Example 1 Step 1 20%Pt / C 0.085 0.881 Comparative Example 1 <h2 style=";text-align:left;direction:ltr"><![CDATA[Pt-Au <h2 style=";text-align:left;direction:ltr"> 0.05 <h2 style=";text-align:left;direction:ltr"> / C-400℃2h]]><h2 style=";text-align:left;direction:ltr"> 0.115 0.891

[0058] It can be seen from Table 1 that after doping with a small amount of G element, the activity of Pt / C catalysts is improved.

[0059] Example 1 Preparation of Pt-Au 0.05 ORR aging test of the catalyst heated at 400℃ for 6h and the 20% Pt / C catalyst prepared in step 1 of Example 1. The ORR polarization diagrams before and after aging are shown in Fig. Figure 8 As shown, the Pt-Au prepared in Example 1 0.05 The mass specific activity of the catalyst prepared at 400℃ for 6h and the 20% Pt / C catalyst prepared in step 1 of Example 1 before and after aging is shown in the figure below. Fig. 9 As shown, from Figure 8 and Fig. 9 It can be seen that Pt-Au 0.05 After aging for 30,000 cycles at 400℃ for 6h, the mass activity of Pt / C decreased by only 6.5%, while that of 20% Pt / C decreased by 38.8% after aging for 30,000 cycles. 0.05 / C-400℃6h stability is much better than 20% Pt / C.

[0060] The Pt-Au prepared in Example 1 0.05 / C-400℃6h catalyst and 20% Pt / C catalyst prepared in step 1 of Example 1 are prepared into electrodes. The method for preparing the electrode is as follows: weigh the catalyst, add the catalyst to a dispersion liquid, wherein the dispersion liquid is a mixture of isopropanol, ultrapure water and nafion solution, and ultrasonically disperse for 2h to obtain a dispersion liquid; then, shear the dispersion liquid in a shearing machine for 0.5h, transfer it to a crusher and crush it for 0.5h to obtain a uniformly dispersed dispersion liquid; add the dispersion liquid to an ultrasonic sprayer, and spray it on a 3×3 (cm) nafion (ion exchange membrane) to obtain a cathode catalyst layer, and the Pt loading in the cathode catalyst layer is 0.1mg cm -2The anode catalyst layer is commercial Pt / C with a Pt loading of 60%. The catalyst layer is assembled into a fuel cell test device and the MEA test is carried out. Fig.10 The Pt-Au prepared in Example 1 0.05 The fuel cell polarization curves of the catalyst prepared at 400℃ for 6h and the 20% Pt / C catalyst prepared in step 1 of Example 1 before and after aging are shown in Table 2. Fig.10 As can be seen from Table 2, Pt-Au 0.05 The peak power density of the catalyst at 400℃ for 6h is higher than that of 20% Pt / C, and its stability in the operation of the fuel cell is also better than that of the 20% Pt / C catalyst.

[0061] Table 2 Pt-Au 0.05 Peak power density of the catalyst heated at 400℃ for 6h and 20%Pt / C catalyst

[0062]

[0063] The G element in the Pt / C surface doped stable metal G catalyst of the present invention is uniformly distributed on the surface of the Pt particles in the form of atomic level; the G atoms can change the electronic structure of the surrounding Pt atoms and improve the activity of the Pt atoms; at the same time, the G atoms can stabilize the surrounding Pt atoms and enhance the stability of the catalyst. In addition, the Pt / C surface doped stable metal G catalyst has good applicability in fuel cell applications and shows good performance in fuel cells.

Claims

1. A Pt / C catalyst doped with a stabilizing metal G on its surface, characterized in that: In the catalyst, G atoms are uniformly distributed on the surface of Pt particles, and G is one or more of Au, Mo and W. The mass percentage of Pt in the catalyst is 10% to 30%.

2. The Pt / C catalyst doped with a stabilizing metal G on the surface according to claim 1, characterized in that: The molar ratio of G atoms to Pt atoms is 1:(100-10).

3. A method for preparing a Pt / C catalyst doped with a stabilizing metal G on the surface as claimed in claim 1, characterized in that: The method proceeds as follows:

1. Preparation of Pt / C catalyst by microwave reduction method; 2. Adsorption of G metal salt: Wet the Pt / C catalyst and place it in the dispersion solution, and stir it ultrasonically until the catalyst is evenly dispersed to obtain a mixed solution A; then add a solution of a stable metal G salt to the mixed solution A, and after the addition is complete, obtain a mixed solution B; ultrasonically treat the mixed solution B for 0.5 to 2 hours, and then stir it at room temperature for 0.5 to 2 hours to make the mixed solution evenly dispersed; then evaporate the mixed solution B in a water bath to obtain a precursor; 3. Preparation of Pt-G / C by annealing and reduction: Place the precursor in a high-temperature furnace, heat it to 200-600°C in a reducing atmosphere and maintain it for 4-10 hours for annealing, cool it to room temperature, grind it evenly, and obtain a Pt / C catalyst with surface doped with stable metal G, recorded as Pt-G / C.

4. The method for preparing a Pt / C catalyst doped with a stabilizing metal G on the surface according to claim 3, characterized in that: The method for preparing Pt / C catalyst by microwave reduction in step 1 is carried out as follows: adding the carbon support to the dispersion and dispersing it evenly, adding chloroplatinic acid solution, stirring evenly and adjusting the pH of the mixed solution to be alkaline; The Pt particles are reduced by microwaves, and after natural cooling, the pH is adjusted to be acidic and stirred for 12 to 24 hours, filtered and cleaned, and then vacuum dried to obtain a Pt / C catalyst; the dispersion liquid is one or more of water, ethanol, methanol, and isopropanol; the carbon powder is XC-72, ECP-600JD or BP-2000.

5. The method for preparing a Pt / C catalyst doped with a stabilizing metal G on the surface according to claim 3 or 4, characterized in that: The dispersion solution described in step 2 is one or more of water, ethanol, methanol, and isopropanol.

6. The method for preparing a Pt / C catalyst doped with a stabilizing metal G on the surface according to claim 3 or 4, characterized in that: The solution of the G metal salt described in step 2 is prepared by dissolving chloroauric acid, gold trichloride, potassium chloroaurate, molybdate, molybdenum pentachloride, tungstate or tungsten hexachloride in a dispersed solution.

7. The method for preparing a Pt / C catalyst doped with a stabilizing metal G on the surface according to claim 3 or 4, characterized in that: In the mixed solution B described in step 2, the concentration of Pt / C is 0.5-2 g / L, and the concentration of the stable metal G salt is 0.00025-0.001 mol / L.

8. The method for preparing a Pt / C catalyst doped with a stabilizing metal G on the surface according to claim 3 or 4, characterized in that: The reducing gas described in step three is a H2 / N2 mixed gas or a H2 / Ar mixed gas, and the volume percentage of H2 in the mixed gas is 3% to 15%.

9. The use of a Pt / C catalyst doped with a stabilizing metal G on the surface as claimed in claim 1, characterized in that: The application is to use the Pt / C catalyst with surface doped stabilizing metal G in the cathode oxygen reduction reaction of fuel cells.

Citation Information

Patent Citations

  • Process for producing high-stability carbon carried Pt-Au bi-metal nano-electro-catalyst

    CN101269327A

  • Rare earth metal Ln doped NC carrier supported PtLn alloy catalyst as well as preparation method and application thereof

    CN116565240A

  • Preparation method of proton exchange film fuel cell electro-catalyst

    CN1832232A

  • Use of catalyst for high temperature proton exchange membrane fuel cell

    CN1937293A

  • De-alloyed platinum nanoparticles

    US20090114061A1